Piagam Madinah: Korelasinya Dalam Menciptakan Masyarakat Majemuk - Rahul; Juanda, Muhamad Aldi; Putri, Risya Nurya Ayyu; Zainal (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2025)
This article examines the correlation of the Medina Charter in creating a pluralistic society. This research seeks to explore the values contained in the Medina Charter, such as tolerance, justice and unity, and relate them to the context of today's multicultural society. The focus of this research is to examine the Medina Charter and its relevance in creating a pluralistic society. This research uses Qualitative research method, the research data is obtained through secondary sources, such as articles and books. The study found that the values embedded in the Medina Charter can guide contemporary society in managing diversity and preventing conflict. The principles contained in the Medina Charter are considered still relevant for today's multicultural society, as they inspired the establishment of a modern constitutional framework that supports the protection of human rights and religious freedom.